Does Maternal Omega 3 Supplementation Protect Against Infantile Hypertrophic Pyloric Stenosis?. Issue 5 (May 2020) - Paran, Maya; Freud, Enrique; Samuk, Inbal; Steiner, Zvi
ABSTRACT: Objectives: Infantile hypertrophic pyloric stenosis (IHPS) is potentially life threatening. The etiology of IHPS remains unknown and many risk factors have been reported. We aimed to assess the prevalence of known risk factors and investigate maternal nutrition and habits as possible additional risk factors for IHPS. Methods: This case-control study includes mothers of infants diagnosed with IHPS and control mothers of infants, age 2 to 11 months, hospitalized in the pediatric department due to other conditions. Cases of IHPS were identified by review of all infants diagnosed with IHPS and operated upon in 2010 to 2016 at 2 major hospitals in central Israel. Data regarding potential risk factors were collected via questionnaires in both study groups. Results: Sixty-six cases and 67 controls were included in the study. Maternal omega 3 supplement consumption during pregnancy was significantly less common among cases of IHPS as compared with controls ( P = 0.031). Consumption of omega 3 supplement was defined as consumption of at least 1 to 2 per week during the pregnancy period. Following adjustment for known risk factors, including male sex and maternal smoking, maternal omega 3 supplement consumption remained associated with a significantly lower risk of developing IHPS (odds ratio = 0.303, 95% confidence interval 0.111–0.828, P = 0.02). Conclusions: Maternal omega 3 supplement consumption during pregnancy was associated with a significantly reduced risk of IHPS. Further studies are needed to support these results and investigate possible mechanisms of the effect of omega 3.